Efektivitas terapi musik dalam menurunkan gejala kecemasan pada pasien gangguan jiwa: A literature review - Amkar, Musvirah Safitri; Abdullah, Rezky Putri Indarwati; Bakhtiar, Ilma Khaerina Amaliyah; Ismail, Muhammad Wirasto; Azis, Uyuni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Mental disorders are chronic conditions with symptoms of anxiety that often arise and impact patients' quality of life. The high prevalence of mental disorders in Indonesia demands effective interventions to manage anxiety. Pharmacological therapy and music therapy are safe and easy-to-apply non-pharmacological options that have been proven to reduce anxiety in various patient groups. Purpose: To describe the mechanism of action of music therapy in reducing anxiety, evaluate previous research findings on music therapy in patients with mental disorders, and provide recommendations for the application of music therapy in psychiatric clinical practice. Method: The literature review study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. The article search design was formulated using PICOS, namely P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study). The literature search was conducted using Google Scholar, PubMed NCBI, ScienceDirect, and Elsevier with the keywords “music therapy” AND “anxiety disorder” AND “psychiatric patients” AND “mental disorder” AND “music intervention” AND “anxiety reduction”. A total of 323 articles were identified and then screened according to the topic of discussion, resulting in 15 selected articles. Results: Music therapy has been proven effective in reducing anxiety symptoms in patients with mental disorders through neurobiological and neuroendocrine mechanisms, namely by decreasing amygdala activation, increasing prefrontal cortex activity, and lowering cortisol levels. Research shows a moderate to large effect (Cohen’s d = 0.74) that is consistent across various diagnoses and ages, with benefits that can last up to 12 months. This therapy is recommended to be conducted 2–3 times per week for a minimum of 8 weeks, combined with conventional therapy and tailored to the patient's preferences and culture. Conclusion: Music therapy is effective in reducing anxiety in patients with mental disorders through neurobiological and neuroendocrine mechanisms. Research shows consistent moderate to large clinical effects across various diagnoses and ages, which can last up to 12 months. This therapy is recommended as a complementary therapy alongside conventional therapy, tailored to the patient's preferences and culture. Keywords: Anxiety Disorders; Mental Disorders; Music Therapy; Therapeutic Intervention. Pendahuluan: Gangguan jiwa merupakan kondisi kronis dengan gejala kecemasan yang sering muncul dan berdampak pada kualitas hidup pasien. Tingginya prevalensi gangguan jiwa di Indonesia menuntut adanya intervensi efektif untuk mengelola kecemasan. Terapi farmakologis, terapi musik menjadi pilihan nonfarmakologis yang aman dan mudah diterapkan, serta terbukti menurunkan kecemasan pada berbagai kelompok pasien. Tujuan: Untuk mendeskripsikan mekanisme kerja terapi musik terhadap penurunan kecemasan, mengevaluasi hasil penelitian terdahulu mengenai terapi musik pada pasien gangguan jiwa, memberikan rekomendasi penerapan terapi musik dalam praktik klinis psikiatri Metode: Penelitian literature review menggunakan metode Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Desain pencarian artikel dengan merumuskan PICOS yaitu P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome) dan S (study). Pencarian literatur yang digunakan berasal dari Google Scholar, PubMed NCBI, ScienceDirect, dan Elsevier dengan kata kunci “music therapy” AND “anxiety disorder” AND “psychiatric patients” AND “mental disorder” AND “music intervention” AND “anxiety reduction”. Mengidentifikasi 323 artikel selanjutnya dilakukan penyaringan sesuai dengan topik bahasan mendapatkan 15 artikel yang dipilih. Hasil: Terapi musik terbukti efektif menurunkan gejala kecemasan pada pasien gangguan jiwa melalui mekanisme neurobiologis dan neuroendokrin, yaitu menurunkan aktivasi amigdala, meningkatkan aktivitas prefrontal cortex, serta menurunkan kadar kortisol. Penelitian menunjukkan efek sedang hingga besar (Cohen’s d = 0.74) yang konsisten pada berbagai diagnosis dan usia, dengan manfaat yang dapat bertahan hingga 12 bulan. Terapi ini direkomendasikan dilakukan 2–3 kali per minggu selama minimal 8 minggu, dikombinasikan dengan terapi konvensional dan disesuaikan dengan preferensi serta budaya pasien. Simpulan: Terapi musik efektif menurunkan kecemasan pada pasien gangguan jiwa melalui mekanisme neurobiologis dan neuroendokrin. Penelitian menunjukkan efek klinis sedang hingga besar yang konsisten pada berbagai diagnosis dan usia, serta dapat bertahan hingga 12 bulan. Terapi ini direkomendasikan sebagai terapi komplementer bersama terapi konvensional dengan penyesuaian terhadap preferensi dan budaya pasien. Kata Kunci: Gangguan Jiwa; Gangguan Kecemasan; Intervensi Terapeutik; Terapi Musik.